1996
DOI: 10.1007/s002849900094
|View full text |Cite
|
Sign up to set email alerts
|

Copper Resistance and Accumulation in the Zygomycete Mucor rouxii

Abstract: Two copper-resistant (Copr) mutants, strains P1 and P3, were obtained from the dimorphic fungus Mucor rouxii. They were characterized as to their ability to take up copper in a growth medium supplemented with this metal ion. Detection of copper by linear sweep striping voltammetry in cell walls and in the cell wall-free fraction of disrupted cells revealed a higher content of the metal in both mutant fractions, as compared with those of the copper-sensitive (Cops) parental strain. Copper binding by M. rouxii g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…These isolates were grown on seven copper sulphate concentrations (0, 0·3, 0·6, 1·2, 2·4, 3·2 and 4·8 m m ). In a previous study with the dimorphic fungus Mucor rouxii , copper sulphate concentrations of 3·2, 4·8 and 6·0 m m were considered to be high, and strains whose spores could germinate and grow on 6·0 m m were considered resistant (Ramirez‐Salgado et al. , 1996).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These isolates were grown on seven copper sulphate concentrations (0, 0·3, 0·6, 1·2, 2·4, 3·2 and 4·8 m m ). In a previous study with the dimorphic fungus Mucor rouxii , copper sulphate concentrations of 3·2, 4·8 and 6·0 m m were considered to be high, and strains whose spores could germinate and grow on 6·0 m m were considered resistant (Ramirez‐Salgado et al. , 1996).…”
Section: Resultsmentioning
confidence: 99%
“…1). Fungi have developed numerous mechanisms for copper resistance (Cervantes & Gutierrez‐Corona, 1994) some of them involving cell wall composition, and in some fungi copper resistance has been related to greater ability of spore germination (Ramirez‐Salgado et al. , 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Elements like copper and zinc are essential micronutrients and may have specific roles in morphogenesis at low and therefore nontoxic concentrations, but some morphological changes may occur at concentrations where some toxicity may be manifest. Earlier studies indicated that living cells of a copper-tolerant strain of M. rouxii accumulated higher amounts of the metal as compared to the metal sensitive parental strain [17,18]. However, no studies on the binding of copper ions by inactivated cells obtained from copper-tolerant and copper-sensitive strains of M. rouxii have been reported when the fungal cells have been cultured under trace and high concentrations of Cu 2ϩ .…”
Section: Introductionmentioning
confidence: 99%
“…The cell wall composition and the chitin content have an important role in tolerance mechanisms in fungi. At 3·2 mmol kg −1 of CuSO 4 , the copper‐resistant strains of Mucor rouxii bounded about 15% more copper in the cell walls than in the cytosol and membranes (Ramirez‐Salgado et al. 1996).…”
Section: Discussionmentioning
confidence: 99%